LEVERAGING SHOPEE LIVE FOR SALES GROWTH: A LITERATURE REVIEW - Harefa, Peni Kristian; Nastiti, Pambayun Kinasih Yekti (PROCURATIO: Jurnal Manajemen & Bisnis, 2024)
The emergence of digitalization has brought new impacts to the business world, particularly in e-commerce. The impact of digitalization has led to more diverse product promotion methods. One example of an e-commerce platform that successfully leverages digitalization is Shopee, through its Shopee Live feature. However, whether live streaming as a product promotion method will be sustainable and what factors determine its success are topics that have not been widely studied. Therefore, the purpose of this study is to identify the key factors driving sales growth on Shopee Live and to determine whether these factors are temporary or sustainable. The method used is a systematic literature review, by reviewing 15 articles that discuss Shopee Live. The results of the study indicate several key factors that can enhance sales on Shopee Live, including the skills of the Shopee Live hosts, direct interaction with buyers, trust in product quality, and the sustainability of product promotions via Shopee Live. This is because the use of Shopee Live has been proven effective in increasing sales.